2016
DOI: 10.1590/0001-3765201620150253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tityus stigmurus (Thorell 1876) (Scorpiones: Buthidae) venom in isolated perfused rat kidneys

Abstract: Scorpions belonging to the Tityus genus are of medical interest in Brazil. Among them, Tityus stigmurus is the main scorpion responsible for stings in the Northeast region. After a sting, the scorpion venom distributes rapidly to the organs, reaching the kidneys quickly. However, there are few studies concerning the renal pathophysiology of scorpion poisoning. In this study, we evaluated the effects of T. stigmurus venom (TsV) on renal parameters in isolated rat kidneys. Wistar rats (n = 6), weighing 250-300 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…In addition, this species has a dorsal serration in the 3rd and 4th follow-up of the metasome and reproduction is paternogenetic, male has a thinner pedipalp and greater metasome than the female. It can be found in the Southeast and Northeast regions, responsible for the highest number of accidents (Silva et al, 2016).…”
Section: Scorpions In Brazilmentioning
confidence: 99%
“…In addition, this species has a dorsal serration in the 3rd and 4th follow-up of the metasome and reproduction is paternogenetic, male has a thinner pedipalp and greater metasome than the female. It can be found in the Southeast and Northeast regions, responsible for the highest number of accidents (Silva et al, 2016).…”
Section: Scorpions In Brazilmentioning
confidence: 99%
“…269,271,272,277 Renal histology shows ATN, glomerular changes, interstitial infiltrate, thrombotic microangiopathy, and CN. 269,272,[276][277][278][279] A casecontrol study in Mexico suggested that scorpion accidents were associated with development of CKD in children. 280 Use of antivenom partially decreased kidney venom concentration in a mice model, and has been associated with more favorable clinical outcome.…”
Section: Leptospirosismentioning
confidence: 99%
“…5 No estado de São Paulo, as três espécies de escorpiões de importância médica são: Tityus serrulatus, ou escorpião amarelo, o mais prevalente, que causa o maior número de acidentes e os de maior gravidade; Tityus bahiensis, ou escorpião marrom, também com potencialidade de causar acidentes graves, porém em menor frequência; e Tityus stigmurus, cujo veneno prejudica principalmente o funcionamento renal. 6 A gravidade do quadro clínico está relacionada à disfunção cardiorrespiratória. 7 A toxina escorpiônica é desprovida de atividade hemolítica e proteolítica.…”
Section: Introductionunclassified